Diseño del cableado estructurado e implementación en el Área de Energía las Industrias y los Recursos Naturales no Renovables, y construcción de un Software de administración de usuarios para internet de la U.N.L. - Carrión Ruilova, Juan Carlos (2008)
This thesis consists of Structured Cabling Design and Implementation in the Area of ​​Energy and Industry and nonrenewable natural resources, and construction management software for Internet Users UNL. This research aims to show the update technology campus network with high availability requirements and speed, defining all technical aspects to be considered for projects structured cabling, from planning to execution, based on the study of standards and standards relevant to this topic. Next, a complete structured cabling design Area is made, taking into account their functional elements, subsystems and space for equipment and cabling distributors, and guidelines are set to be followed for implementation. In other an adaptation and improvement of the existing network is performed on the Area Administration Building (Building 1), which is run in coordination with the Ing. Juan Carlos Torres (Network Manager AEIRNNR). Clarifying that the design initially proposed by the research group was not implemented; As work addressing the emergency needs of the building network. Finally a system of control and management of access to the Web, "Manager Proxy" is developed using object-oriented technologies. Based on the analysis, design, modeling, coding, application, and data is provided for implementation. To sustain described above are made to the software user manuals and programmer's manual, and part of a proposed structured cabling wiring design. These copies are attached to this thesis.